Comparative Phytochemical and Antimicrobial Analyses of Siphonochilus aethiopicus and Monodora myristica (Acta Scientiarum. Biological Sciences, 2025)
Medicinal plants are used as interventions and alternatives in many countries including Africa. The phytochemicals produced by plants possess potential antimicrobial activities against pathogens through various mechanisms of action. This study aimed to compare the phytochemical and antimicrobial constituents of rhizomes of Siphonochilus aethiopicus (African ginger) and seeds of Monodora myristica (African nutmeg). The rhizomes of S. aethiopicus and seeds of M. myristica were separately and thoroughly washed, peeled, sliced, room-dried and ground. The crude extracts of the plants were obtained using aqueous and methanol as solvents according to standard procedures while the phytochemical constituents were also evaluated using standard methods. The antimicrobial activities of the extracts were determined using the agar-well diffusion method. The bacterial species investigated were Escherichia coli, Enterococcus faecalis, Klebsiellla pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, while the fungal species were Aspergillus flavus, Aspergillus glaucus, Candida albicans, Candida tropicalis, Trichophyton mentagrophytes and Trichophyton rubrum. The plant extracts contained alkaloids, saponins, phenols, flavonoid, tannin, phytate, terpenoids and cyanogenic glycoside in varying qualities and quantities. The extracts of the plants exerted antimicrobial effects against the test organisms. There was a significant difference between the antibacterial activities at 12.5 and 25 mg mL-1 concentrations (p = 0.022). The study revealed that the phytochemical components and antimicrobial properties of M. myristica extracts exhibit comparatively greater potency than those of S. aethiopicus, though the variances were not found to be statistically significant. The extracts of these plants could be purified, formulated and standardized for the production broad-spectrum antimicrobial agents.